Valuation of Stpotify Technology SA - Estrada Argeñal, Jorge Armando; Sieber, Patrik, 1977-; Ali, Tanweer; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
In this thesis we aim to make a valuation of the company Spotify Technology S.A. We will utilize different method of valuation, and as well a complete strategic analysis to understand how the industry works, and how Spotify is able to generate revenue through their different methods. Through this method we will empathizes in the forecast of the future share price of Spotify Technology S.A. by utilizing methods such as the Discounted cash flow mode, Weighted average cost of capital, Net Working Capital, and Capital Expenditure. The thesis will delve deeper as well into the music streaming industry by showcasing and analyzing every aspect Spotify Technology S.A. faces to become a profitbale and recognized company.
Vedoucí práce: Patrik Sieber
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses